Design of Coil Patterns for an Axial Flux Permanent Magnet Synchronous Motor With PCB Stator - Dong-Woo Nam; Min-Ki Hong; Na-Rim Jo; Dong-Hoon Jung; Won-Ho Kim (IEEE Access)
Recently, the demand for miniaturization in various applications within the automotive and industrial sectors has been steadily increasing. Consequently, there is a growing need for research and development of the Axial Flux Permanent Magnet Synchronous Motor (AFPMSM), which is advantageous in thin structures. However, in conventional AFPMSMs, the variation in tooth thickness from the inner diameter to the outer diameter of the stator poses significant manufacturing challenges. To address this, a Coreless AFPMSM, which does not use a stator core, can be employed. However, this design introduces its own challenges, including significantly increased magnetic reluctance due to the absence of teeth and the need for robust support structures for the stator windings. This paper proposes a solution to these issues by utilizing a Printed Circuit Board (PCB) substrate as the stator in a PCB Stator Motor. It describes the design process for the coil pattern of the PCB stator. Using conventional winding methods, the coil pattern layout of the PCB stator is designed, effective conductors are arranged and connected, and the PCB stator is completed. The PCB stator is then applied to an AFPMSM, with Halbach permanent magnets used to improve power density. The design is carried out using 3D finite element analysis (FEA), and the proposed model is validated by comparing the back electromotive force (EMF) under no-load conditions with that of the manufactured model.